PENGEMBANGAN E-LKPD SCAFFOLDING BERBASIS ANDROID MATERI TUMBUHAN, SUMBER KEHIDUPAN DI BUMI UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR (SISWA KELAS IV SDN PAPUNGAN 2 KABUPATEN BLITAR) - Setya Ningrum Nailul Hidayah; Mohamad Fatih; Cindya Alfi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
To improve the learning independence of fourth-grade students at SDN Papungan 2, Blitar Regency, this study attempts to create an Android-based E-LKPD software on the topic "Plants, the Source of Life on Earth." The ADDIE paradigm, which consists of five stages—analysis, design, development, implementation, and evaluation—was applied in this study using a research and development (R&D) approach. A student learning independence questionnaire, expert validation, interviews, and observations were among the methods used to collect data. The validation results showed that the E-LKPD was classified as highly valid with scores from material experts of 82%, media experts 75%, and language experts 86%. The effectiveness test using N-Gain analysis showed an average increase in the independence score of 7.54%, which is considered low but indicates an increase because the independence aspect is affective and develops gradually. In addition, the results of the student learning independence questionnaire after using the E-LKPD showed a percentage of 93%, which is classified as very good. Thus, this scaffolding-based E-LKPD is declared feasible, effective, and strengthens students' skills in managing learning independently.